Predicting factors for the pattern of intravenous immunoglobulin utilization in a middle eastern university hospital - Zeinab Fakhari; Shadi Farsaei; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2018)
Objective: The dramatic increase in the consumption of intravenous immunoglobulin (IVIG) products in nonapproved indications, its high cost, and the severe shortage has developed the concerns of its irrational utilization, especially in the Middle East countries. Therefore, this clinical study attempts to describe the pattern of IVIG administration in one of the largest hospitals in Iran and find the variables associated with inappropriate IVIG utilization. Methods: This cross-sectional medication utilization study was conducted in one of the largest referral hospitals in Iran. Random IVIG administrations were assessed from different wards for 9 months. Different data were collected to evaluate the pattern of IVIG administration and find variables, which could predict this behavior. Findings: IVIG was prescribed for approved indications in 72% of 201 patients recruited in our study. Although, the rate of drug administration was appropriate in most of the study population, hydration and pre-medication were unsuitable in more than one-third of the patients. Among the variables analyzed to find the factors affecting the misuse of IVIG, female gender, older age of patients, and longer time to start IVIG administration due to hospital admission were statistically significant in the multivariate model. Conclusion: Despite the fact that inappropriate use of IVIG was confirmed in less than 30 % of its utilization for the studied patients, it caused a potential risk of treatment complications and a notable and unjustifiable burden of unnecessary costs for this University hospital.